City Waste Compost and Sustainability of Rice-Wheat Cropping System (Nepal Agriculture Research Journal, 2009)
An experiment was conducted on Rhodic Ustochrept soil in Central Hill of Nepal growingwheat-mungbean-rice in rotation. Grain yields as affected by 28 t ha-1 a of town compost werecompared with the same amount of farmyard manure and N:P:K (120:60:40). NPK producedsignificantly higher wheat grain (3897 t ha-1). Other yield results were at par with one another.NPK produced lowest mungbean yield. After growing second crop fertility seems to beexhausted thus rice yield indicated no notable residual fertilising effect. FYM and town compostleft noteworthy amounts of P, Ca, Mg and K even after rice harvest.Key words: Organic manure; plant nutrients; sustainabilityDOI: 10.3126/narj.v7i0.1868Nepal Agriculture Research Journal Vol.7 2006 pp.49-53